2018
DOI: 10.53331/teq.v1i3.5419
|View full text |Cite
|
Sign up to set email alerts
|

Conflictos ambientales en la producción apícola: resistencia maya ante la agricultura corporativa en la península de Yucatán

Abstract: After the meaning of apiculture for indigenous Maya peasants in the Yucatán Peninsula, we analyze the case that drove grassroots organizations and indigenous communities to get together for promoting a legal demand to stop large plantations of transgenic soy. Mexican Government promoted the plantations the since the last decade of the past century, affecting peasant traditional agriculture and apiculture. The demand was against the Mexican Government, but aiming at the transnational corporation Monsanto, evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…3b), which were consistent with the infrared spectrum analysis reported in the literature. 55 This study indicated the successful preparation of HKUST-1-CM and that the crystal structure was not affected after modification with stearic acid. The presence of distinct absorption peaks at 2850 and 2922 cm −1 (red shaded part in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…3b), which were consistent with the infrared spectrum analysis reported in the literature. 55 This study indicated the successful preparation of HKUST-1-CM and that the crystal structure was not affected after modification with stearic acid. The presence of distinct absorption peaks at 2850 and 2922 cm −1 (red shaded part in Fig.…”
Section: Resultsmentioning
confidence: 62%